Enhancing Critical Thinking with Gen AI: A Literature Review - Hikmawati, Agci; Mohammad, Nhelbourne K. (Buletin Edukasi Indonesia, 2025)
The emergence of generative artificial intelligence (Gen AI) has sparked transformative changes across educational landscapes, with critical thinking emerging as a central skill enhanced by these technologies. This literature review explores the adoption and application of Gen AI tools, such as ChatGPT and AI-enhanced systems, in fostering critical thinking skills within higher education. Synthesizing recent research, the review examines the role of AI in collaborative learning, academic writing, and innovative pedagogical approaches, highlighting its ability to support soft skills development, enhance peer-based learning frameworks, and redefine assessment practices. Using a thematic analysis approach, this study categorizes findings into critical areas, including the role of Gen AI in developing cognitive skills, its collaborative potential, and its integration into future-ready educational frameworks. While these tools offer unprecedented opportunities for creativity, accessibility, and engagement, they also present challenges, including bias, ethical considerations, and reliance on AI-generated outputs. The review concludes by outlining future research directions, emphasizing the need for stakeholder-driven frameworks to fully leverage Gen AI’s potential while safeguarding its responsible use in educational contexts. This study underscores the transformative potential of Gen AI in nurturing 21st-century critical thinking skills and calls for continued interdisciplinary inquiry to navigate its complex implications.